A study on stress in Indian 2nd year homoeopathy students by perceived stress score (PSS), clinical parameters and EMG activity. - DR TUSHAR J. PALEKAR; SHILPA D. KHANDARE; DR DHARMENDRA SHARMA; DR P.A. CHAPHEKAR (International Journal of Pharma and Bio Sciences, 2017)
A certain amount of stress is desirable to give the required stimulation and motivation. However, too much of stress adversely affects health and well-being, behaviour etc. Aim of the study was to assess Perceived stress in 2nd year BHMS students of Homoeopathy with assessment of corroborative clinical parameters, perceived stress score (PSS) and Electromyography activity (EMG) activity. A cross-sectional survey were carried out amongst undergraduate 2nd year homeopathy students of Dr. D. Y. Patil Homoeopathic Medical College, Pune, India. On the basis of the PSS score ≥ 20, 35 participants were identified to be in moderate + category of stress. 50 students from the second year respondents participated in this study. The mean age of the study participants were found to be 19.71± 0.926 respectively, with a range of 18-23 years. The majority of participants were female (88.57%). Mean PSS score of all 35 participants were seen to be 22.57±2.24. High levels of perceived stress were found in Homeopathic students. All Subjects received 10 sessions of EMG biofeedback training for 10 minutes for 5 days/week for 2 weeks.